Severe disease in patients with rheumatoid arthritis carrying a mutation in the Mediterranean fever gene. Issue 7 (15th June 2005) - Rabinovich, E; Livneh, A; Langevitz, P; Brezniak, N; Shinar, E; Pras, M; Shinar, Y
Abstract : Background: Pyrin is a newly recognised intracellular regulator of inflammation, and mutations in MEFV, the gene encoding pyrin, are the cause of familial Mediterranean fever. Objective: To determine if known mutations of MEFV are associated with rheumatoid arthritis (RA) morbidity or can modify RA severity. Methods: The frequency of the three most common MEFV mutations: M694V, V726A, and E148Q, was determined in 98 Israeli patients with RA (74 women, 24 men) and compared with that in 100 healthy subjects matched for origin. RA severity was determined using a new clinical score of 126 grades. The median severity score of mutation carrier and non-carrier groups was compared after confounding measures were eliminated by logistic regression. Results: 17/98 (17%) patients with RA (all women) were heterozygous for common MEFV mutations, predominantly E148Q (12 patients), and one patient was homozygous for the V726A mutation. The overall mutation rate was comparable between patients with RA and healthy subjects. Patients carrying a mutation had a higher median severity score than the non-carrier group (42 v 29, p = 0.0005). The logistic regression model assigned a 15-fold odds ratio for severe RA in carriers, after adjusting for sex, presence of rheumatoid factor, age at onset, and disease duration (n = 97, p = 0.01, 95% CI 1.74 to 128). Conclusion: MEFV, and particularly the E148Q mutation, is an independent modifier of the clinical manifestations of RA. This is the second Th1-type autoimmune disease in which MEFV mutations have been shown to aggravate the clinical status.